TAXPAYER AWARENESS IN EFFORTS TO ACHIEVE TAXPAYER'S TARGETBUILDING EARTH (PBB) IN TOLOTIO VILLAGEBONEPANTAI DISTRICT BONE BOLANGO DISTRICT - Piyohu, Saripin; S.Mooduto, Willian Indra; Anani, Siske (Jurnal Ilmu Manajemen dan Bisnis, 2024)
The aim of the research report : This research aims to determine the factors inhibiting public awareness in achieving the land and building tax (PBB) target in Tolotio Village. Research method : The method in this research uses triangulation data collection techniques consisting of observation, interviews and documentation. Research results: The research results show that in Tolotio Village it cannot be said to be good compared to previous years because according to research there is still a lack of public awareness in achieving the property tax target . This is caused by the mechanism for submitting SPPT which is not good , there are economic factors which make it difficult for people to pay land and building taxes.